Synthesis of a series of new ruthenium organometallic complexes derived from pyridine‐imine ligands and their catalytic activity in oxidation of secondary alcohols. (21st December 2018) - Hao, Zhiqiang; Li, Ying; Li, Chen; Wu, Ruitao; Ma, Zhihong; Li, Suzhen; Han, Zhangang; Zheng, Xuezhong; Lin, Jin
Abstract : Reactions of pyridine imines [C5 H4 N‐2‐C(H) = N‐C6 H4 ‐R] [R = H (1), CH3 (2), OMe (3), CF3 (4), Cl (5), Br (6)] with Ru3 (CO)12 in refluxing toluene gave the corresponding dinuclear ruthenium carbonyl complexes of the type μ ‐ η 2 ‐CH[(2‐C5 H4 N)(N‐C6 H4 ‐R)]2 Ru2 (CO)4 ( μ ‐CO) [R = H (7); CH3 (8); OMe (9); CF3 (10); Cl (11); Br (12)]. All six novel complexes were separated by chromatography, and fully characterized by elemental analysis, IR, NMR spectroscopy. Molecular structures of 7, 10, 11, and 12 were determined by X‐ray crystal diffraction. Further, the catalytic performance of these complexes was also tested. The combination of μ ‐ η 2 ‐CH[(2‐C5 H4 N)(N‐C6 H4 ‐R)]2 Ru2 (CO)4 ( μ ‐CO) and NMO afforded an efficient catalytic system for the oxidation of a variety secondary alcohols. Abstract : Synthesis, structure and catalytic activity of a series of new ruthenium organometallic complexes derived from pyridine‐imine ligands were researched.